The oxytocin system of mice and men: similarities and discrepancies of oxytocinergic modulation in rodents and primates - Althammer, Ferdinand; Jirikowski, Gustav; Grinevich, Valéry (Peptides, 2018)
Nonapeptides and their respective receptors have been conserved throughout evolution and display astonishing similarities among the animal kingdom. They can be found in worms, birds, fish, amphibians, reptiles and mammals, including rodents, non-human primates and humans. In particular, the neuropeptide oxytocin (OT) has attracted the attention of scientists due to its profound effects on social behavior. However, although both the neuropeptide and its receptor are identical in rodents and primates, the effects of OT vary greatly in the two species. Here, we provide a brief overview about OT’s role in the evolution of mammals and provide reasons for the manifold effects of OT within the brain with a particular focus on the discrepancy of OT’s effects in rodents and primates. In addition, we suggest new approaches towards improvement of translatability of scientific studies and highlight the most recent advances in animal models for autism spectrum disorder, a disease, in which the normal function of the OT system seems to be impaired.
Gesehen am 08.05.2020